The central limit theorem for sums of the renewal processes - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Алешкявичене. Центральная предельная теорема для сумм процессов восстановления A. Aleškevičienė. Centrinė ribinė teorema atstatymo procesų sumoms